Pengaruh Lingkungan Kerja Non Fisik, Kompensasi, Beban Kerja terhadap Turnover Intention Gen Z - Izza Haniyah; Anwar Azazi; Dody Pratama Marumpe; Ilzar Daud; Efa Irdhayanti (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The participation of Generation Z in the contemporary labor market serves as a key catalyst in driving technological adoption, organizational innovation, and changes in work culture. However, the high turnover intention among this generation indicates instability in employee retention, which can impact operational efficiency and continuity, particularly in the service sector. This study aims to empirically examine the influence of Non-Physical Work Environment, Compensation, and Workload on Turnover Intention among Generation Z workers in the Coffee Shop industry in Pontianak City, with Job Satisfaction as a mediating variable. A quantitative approach was employed in this study, with data collected through an online questionnaire using a five-point Likert scale. A total of 200 respondents aged 18–27 years were selected using purposive sampling based on relevant criteria. Data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach via the SmartPLS 4 software. The analysis results show that the Non-Physical Work Environment has a significant negative effect on Turnover Intention, while Compensation has a negative but not significant effect. Workload has a significant positive effect on Turnover Intention. Furthermore, the Non-Physical Work Environment and Compensation have significant positive effects on Job Satisfaction, while the effect of Workload is not significant. Job Satisfaction is proven to act as a significant mediator in the relationship between the Non-Physical Work Environment and Compensation on Turnover Intention, but it does not mediate the relationship between Workload and Turnover Intention. These findings emphasize the urgency of formulating managerial strategies focused on improving the quality of the work environment and implementing adaptive compensation policies, in order to sustainably reduce turnover rates among Generation Z workers.